A method for selecting optimal sections for members of skeletal structures - Nha, Chu Duc (Vietnam Journal of Mechanics, 2001)
This paper presents a simple method for selecting optimal sections for members of skeletal structures from an initially given set of sections. This is an extension of evolutionary structural optimization (ESO) to the sizing optimization problem with discrete design variables. Member sensitivity index for section sizing is derived from the optimality criterion. Optimization process is an iterative process of analysis, sensitivity calculation and section selection until optimality criterion is satisfied or constraints are violated. The proposed optimization procedure has been implemented into a structural analysis and optimization program called FEMOPT written on MATLAB programming language. Illustrative examples demonstrate the effectiveness of the proposed method.